LETUSAN KRAKATAU 1883: PENGARUHNYA TERHADAP GERAKAN SOSIAL BANTEN 1888 - Erlita Tantri (Jurnal Masyarakat dan Budaya, 2014)
This paper aims to explain the Krakatau explosion in 1883 and its impact, mainly on the 1888 social movement in Banten. Krakatau explosion in 26-27 August 1883 was one of the tremendous volcano explosions in the 19th century, after the Tambora explosion in 1815. The impacts of explosion, such as high tsunami wave, ash, gas covered the atmosfer, had given other impacts on social, political, and economic aspects, as well as scientific sphere. Climate change affecting the ecology, such as the increase of death because of starvation and diseases, increase religion fanatism. This religious fanatism generated the social movement in Banten peaking in 1888. Keywords: volcanoes, Krakatau, Banten, religious fanaticism, social movement.